(untitled) (Journal of the Management Sciences, 2023)
The study determined the relationship between employee retention and performance of selected banks in Awka, Anambra State. The specific objectives focused on the degree of relationship that exists between employee compensation and quality service delivery; secondly, the extent of relationship that exists between job security and business advantage of selected banks in Awka, Anambra State. The study was anchored on Resource-based theory by Barney (1991). The study adopted descriptive survey research design and the population of the study was 135 staff representing GTCO Plc, Zenith Bank Plc and UBA Plc in Awka, Anambra State. Hypotheses were tested using Pearson Product Moment Correlation Coefficient with the aid of SPSS version 27. Findings revealed that there is positive relationship between employee retention and performance selected Banks in Awka, Anambra State by indicating positive relationship between employee compensation and quality service delivery; secondly, between job security and business advantage. The study concluded that employee retention strategies such as employee compensation and job security can result in sustainable performance of banks. The study recommended that management should adopt variable compensation packages so as to keep employees in suspense as they work with the organization. This will result in achieving quality service delivery.